Isolasi Dan Karakterisasi Bromelain Bonggol Nanas Dari Limbah Industri (Ananas comosus L. Merr.) - Mulyani, Laida Neti; Larasti, Veny; Handayani, Dwi; Herlina, Herlina (JURNAL FARMASI GALENIKA, 2024)
Waste of pineapple stem (Ananas comusus L. Merr.) has not been optimally utilized, although it is known that pineapple contain bromelain enzym. This research aimed to isolation and characterization bromelain from pineapple stem. Enzim was extracted from pineapple stem to produce crude enzim of bromelain. Isolation bromelain was done by amonium sulphate precepititation and continued by dialysis. Characterization to determined molecular weight, protein content and protease activity. The result of fractionation by amonium precipitation showed the highest specific activity on amonium sulphate 40-60% fraction 1011,98 U/mg. Caharacterization of purified bromelain showed that molecular weight of bromelain is 23,69 dan 24,72 kD with proteint content 2,78 mg/mL and protease activity is 2833,33 U/mL. This study concluded that the pineapple stem has bromelain enzym with the protease activity.